Maintenance of pre‐existing DNA methylation states through recurring excess‐light stress. (16th May 2018) - Ganguly, Diep R.; Crisp, Peter A.; Eichten, Steven R.; Pogson, Barry J.
Abstract: The capacity for plant stress priming and memory and the notion of this being underpinned by DNA methylation‐mediated memory is an appealing hypothesis for which there is mixed evidence. We previously established a lack of drought‐induced methylome variation in Arabidopsis thaliana (Arabidopsis); however, this was tied to only minor observations of physiological memory. There are numerous independent observations demonstrating that photoprotective mechanisms, induced by excess‐light stress, can lead to robust programmable changes in newly developing leaf tissues. Although key signalling molecules and transcription factors are known to promote this priming signal, an untested question is the potential involvement of chromatin marks towards the maintenance of light stress acclimation, or memory. Thus, we systematically tested our previous hypothesis of a stress‐resistant methylome using a recurring excess‐light stress, then analysing new, emerging, and existing tissues. The DNA methylome showed negligible stress‐associated variation, with the vast majority attributable to stochastic differences. Yet, photoacclimation was evident through enhanced photosystem II performance in exposed tissues, and nonphotochemical quenching and fluorescence decline ratio showed evidence of mitotic transmission. Thus, we have observed physiological acclimation in new and emerging tissues in the absence of substantive DNA methylome changes. Abstract : DNA methylation is considered to facilitate environmental acclimation in an epigenetic manner. However, there are conflicting reports regarding the ability for an individuals' methylome to be shaped by environmental factors. A key finding here is that the Arabidopsis methylome is impervious to excess‐light induced changes despite the observation of excess‐light stress priming. Furthermore, newly formed leaves post 1‐week of recovery show altered NPQ characteristics than nontreated counterparts or older leaves of primed plants, giving evidence of DNA methylation independent memory.